Predisposing Factors and Coping with Musical Performance Anxiety Among Professional Musicians - Gómez-López, Belén; Sánchez-Cabrero, Roberto (Universitas Negeri Semarang, 2025)
Musical performance anxiety (MPA) is a psychopathological condition with a notably high prevalence among both music students and professional musicians. Despite growing awareness of its impact, there is still a need to identify the specific predisposing factors and the most effective strategies for coping with this condition. The present study seeks to investigate the relationship between varying levels of musical performance anxiety and a range of attributive characteristics among musicians. Furthermore, it aims to examine the preventive and coping strategies employed by those affected. A quantitative study was conducted with a sample of 108 participants, from whom sociodemographic information was collected, along with self-reported perceptions of anxiety and responses to the K-MPAI-R questionnaire, a validated instrument for measuring MPA. The findings suggest that individuals professionally engaged in classical music report significantly higher levels of performance anxiety compared to those involved in other musical styles. Among the coping mechanisms reported, breathing exercises, self-motivation strategies, and distraction techniques emerged as the most frequently used. Interestingly, the use of meditation as a coping strategy was found to be positively associated with elevated levels of anxiety. These results carry important practical implications, particularly in guiding targeted interventions for the prevention and effective management of musical performance anxiety in both professional and educational settings.